Bidirectional Dual Active Clamping Push-pull Dc-dc Converter - Souza, Eduardo Valmir de; Waltrich, Gierri; Barbi, Ivo (Eletrônica de Potência, 2016)
In this paper is presented a bidirectional dual active clamping push-pull dc-dc converter, to be used in applications which require isolated bidirectional interface between two dc ports with low-voltage/low-current ripple. The main characteristics of the proposed converter are the non necessity of input and output filters in both ports, galvanic isolation, reduced number of magnetic components and high efficiency operation. The paper presents a theoretical analysis of the proposed converter and experimental analysis for a 600W prototype, with 50kHz switching frequency, and dc power supplies of 14 and 42 volts, at the input and output ports, respectively. The measured performance agreed well with the theoretical predictions.